Industri Halal di Aceh: Strategi dan Perkembangan - Ramadhan Razali; Angga Syahputra; Almira Keumala Ulfah (AL-QARDH, 2021)
This study aims to analyze the strategy and development of the halal industry in the province of Aceh. This research is qualitative research, using a literature review approach from various previous studies. This study uses secondary data obtained from journals, documentation, books, and reports from related parties such as the literally Central Agency on Statistics, LPPOM MPU, LPPOM MUI, Aceh Culture and Tourism Office, and related parties.The results of the study found that Aceh Province is one of the provinces that implement sharia in all sectors. The application of Islam is not only in banking but is also applied to tourism, food, and other halal industries, however, the optimization of the halal industry cannot be felt optimally. The development of a halal industry strategy needs support from the local government. One strategy that must be done is to issue a halal certificate easily but professionally. In addition, to maximize the halal industry, especially halal tourism, local governments must also pay attention to the existing infrastructure. With the maximum development strategy carried out, it is expected to increase the halal industry, especially halal tourism in Aceh Province